Algae: biodiversiti, influencial parameters and the applications - Natanamurugaraj, Govindan; M. M., Yusoff; Gaanty Pragas, Maniam (Penerbit UMP, 2017)
Research on Algae is now a more important subject in this era of marine biology and biotechnology. Marine biologists are trying to understand the function of algae and its uses in all aspects of biological and biomedical approaches. Finding algal potentials is correlated with identification of microalgae in a particular environment for its antibacterial activities, antioxidant activities, nutrient enrichments, synthesizing nano particles, separation of bioactive compounds and secondary metabolites, identification of polysaccharides, biodiesel production, identification of toxin producing microalgae and lipids production for various health supplements and so forth which can be corroborated with algae observations